Spanish Version of the Revised Mental Health Inventory-5 (R-MHI-5): New Psychometric Evidence from the Classical Test Theory (CTT) and the Item Response Theory Perspective (IRT) - Vilca, Lindsey W. (2021)
ABSTRACT The study’s objective was to evaluate the psychometric properties of the revised version of the MHI-5, for which a sample of 1002 university students of both sexes (41.4% men and 58.6% women) between the ages of 17 to 35 years (M = 21.4; SD = 3.4) was collected. Along with the R-MHI-5, other instruments were applied to measure anxiety and depression. Regarding the results, it was evidenced that the model with two related factors presents better fit indices (CFI = .99; TLI = .99; RMSEA = .071) compared to a one-dimensional model (CFI = .74; TLI = .48; RMSEA = .422). Also, it was found that the factorial structure of the MHI-5 did not show evidence of being strictly invariant for the group of men and women. However, it did show evidence of partial invariance for the group of adolescents and adults. Furthermore, the latent relationships model showed that psychological well-being is negatively related to anxiety (− .25) and depression (− .37), and psychological distress is positively related to anxiety (.85) and depression (.87). From the IRT perspective, all items present adequate discrimination indices, with item 4 being the most accurate item to assess psychological well-being. Regarding psychological distress, items 3 and 5 are the most accurate to assess this dimension. It is concluded that the scale that the R-MHI-5 is an instrument with robust psychometric evidence from the perspective of CTT and IRT.